Effects of Collaborative Care for Comorbid Attention Deficit Hyperactivity Disorder Among Children With Behavior Problems in Pediatric Primary Care. (July 2020) - Kolko, David J.; Hart, Jonathan A.; Campo, John; Sakolsky, Dara; Rounds, Jeffrey; Wolraich, Mark L.; Wisniewski, Stephen R.
This study evaluates the impact of a 6-month care management intervention for 206 children diagnosed with comorbid attention deficit hyperactivity disorder (ADHD) from a sample of 321 five- to 12-year-old children recruited for treatment of behavior problems in 8 pediatric primary care offices. Practices were cluster-randomized to Doctor Office Collaboration Care (DOCC) or Enhanced Usual Care (EUC). Chart reviews documented higher rates of service delivery, prescription of medication for ADHD, and titration in DOCC (vs EUC). Based on complex conditional models, DOCC showed greater acute improvement in individualized ADHD treatment goals and follow-up improvements in quality of life and ADHD and oppositional defiant disorder goals. Medication use had a significant effect on acute and follow-up ADHD symptom reduction and quality of life. Medication continuity was associated with some long-term gains. A collaborative care intervention for behavior problems that incorporated treatment guidelines for ADHD in primary care was more effective than psychoeducation and facilitated referral to community treatment.